Leveraging Blockchain Technology to Enhance Security in the Banking Services Sector - Maharjan, Mahesh; Chandra Thakur, Pratik (MVIC Journal of Management and Information Technology, 2025)
The banking sector faces unprecedented cybersecurity challenges, with traditional centralized systems proving vulnerable to sophisticated attacks resulting in billions of dollars in losses annually. This research investigates how blockchain technology can revolutionize banking security infrastructure while enhancing operational efficiency and transparency. Through a mixed-methods approach combining systematic literature review and empirical analysis, this study reveals that blockchain implementation can reduce operational costs by up to 70%, improve transaction processing from days to minutes, and significantly strengthen security against cyber threats. However, regulatory compliance, scalability issues, and integration complexities remain significant adoption barriers. The research proposes a comprehensive framework for blockchain implementation that addresses these challenges while maximizing the technology’s transformative potential for global banking systems.